A Comparative Study of Instrument Assisted Soft Tissue Mobilization Versus Myofascial Release for the Treatment of Mechanical Neck Pain in Dentists - Palekar, . Tushar J; Tandon, Vanshika; Tandon, Vanshika; Mulchandani, Kiran; Belekar, Ketaki; Basu, Soumik (Journal of Neonatal Surgery, 2025)
Background: Mechanical neck pain (MNP) is a prevalent occupational health concern among dentists due to sustained postures and repetitive movements. Instrument-Assisted Soft Tissue Mobilization (IASTM) and Myofascial Release (MFR) are widely used techniques for managing MNP, but their comparative effectiveness remains unclear. Objective: To evaluate and compare the effectiveness of IASTM with an exercise program versus MFR with an exercise program in improving pain, cervical range of motion (ROM), posture, and disability in dentists with MNP Participation Information and Methods A total of 72 dental practitioners (aged 20–40 years) with mechanical neck pain were recruited via purposive sampling and randomly assigned to Group A- IASTM + therapeutic exercises and Group B- MFR + therapeutic exercises. Interventions were conducted every alternate day for two weeks. Outcome measures included Numeric Pain Rating Scale (NPRS), Neck Disability Index (NDI), Craniovertebral Angle (CVA), and cervical ROM. Results- Both groups showed significant improvements (p < 0.001) in pain, ROM, Craniovertebral Angle and functional ability. IASTM demonstrated superior pain reduction (NPRS: 0.86 ± 0.68) compared to MFR (1.25 ± 0.60, p = 0.013). Whereas no significant differences were found in ROM, posture, or NDI between the groups (p > 0.05). Conclusion- IASTM and MFR are equally effective in improving range, posture and functional outcomes, with IASTM showing a slight advantage in pain relief. Future studies should explore long-term efficacy and can also compare effectiveness with Ergonomic Training on neck pain..